Role of serum hepcidin as a marker of iron overload in beta thalassemia major - P., Chaithra; A., Pragalatha Kumar; G., Aruna; L., Hemalatha (International Journal of Contemporary Pediatrics, 2023)
Background: Beta thalassemia major (BTM) is the most common hemolytic anemia. Regular blood transfusion is a basic treatment modality, recurrent blood transfusion which leads to iron overload and its complications. Hepcidin hormone is found to be a key regulator of iron homeostasis and is significantly increased in children of BTM with iron overload. The main objective of the study is to find out the role of serum hepcidin as a potential marker of iron overload in children with BTM, and to correlate the relationship between serum hepcidin and serum ferritin level in BTM children. Methods: This was a hospital based prospective observational study conducted at Indira Gandhi institute of child health for 12 months from January 2019 to December 2019. Included 100 children between age group of 2 months to 18 years diagnosed with BTM on blood transfusion and 50 age and sex matched healthy controls. Results: In the study group 70% children had >5 transfusions. The median serum hepcidin level (2.354 ng/ml) was significantly higher among those with higher number of total transfusions (>5 transfusions). In addition, hepcidin level showed good positive correlation with total number of transfusions (r=0.608, p<0.001). Also, serum hepcidin showed positive correlation with serum ferritin levels with 87% sensitivity and 88% specificity which was statistically significant (r=0.749, p<0.001). Conclusions: In the present study, BTM children who received >5 transfusions serum hepcidin level was significantly elevated and serum hepcidin showed positive correlation with serum ferritin levels. Thus, hepcidin can be considered as a potential marker of iron overload in patients with BTM.